Impact of COVID-19 pandemic on relapse of individuals with severe mental illness and their caregiver's burden - Sara Nooraeen; Shahrzad Bazargan-Hejazi; Morteza Naserbakht; Camelia Vahidi; Farideh Shojaerad; Seyedeh Sahar Mousavi; Seyed Kazem Malakouti (Frontiers Media S.A., 2023)
BackgroundThe implementation of quarantine and social distancing measures to control the COVID-19 pandemic led to restrictions at the community level and most of in-person psychiatric services were discontinued. This situation could affect the psychopathology of the patients and the burden of their caregivers. The aim of this study was to investigate the effects of COVID-19 pandemic on people with severe mental illnesses (SMIs) and their caregivers' burden.MethodThe study sample consisted of 86 patients with severe mental illness and 86 caregivers. The mental status, relapse rate, and rehospitalization rate of the patients and the general health status and burden of caregivers were investigated in three waves, including before and 3 and 6 months after the COVID-19 pandemic.ResultsThe relapse rate of the patients was 14%, 33.7%, and 43% (p = 0.000) and the rehospitalization rate was 4.7%, 7%, and 10.5% in waves 0, 1, and 2, respectively (p = 0.000). Most of the psychopathological scales increased in three waves (p = 0.000). The caregivers' burden and health condition worsened during the nine months of the study as well (p = 0.000).ConclusionThe COVID-19 pandemic led to the exacerbation of symptoms and increased the relapse rate in people with SMIs. It also worsened the caregivers' condition. People with severe mental illnesses (SMIs) and their caregivers are one of the most vulnerable groups on which the COVID-19 pandemic had a marked negative effect.